Comparison of endoscopic ultrasound-guided tissue acquisition using 22 G versus 20 G procore needles in solid lesions: a pilot study - Ahmed Altonbary; Hazem Hakim; Doaa Bakr; Ahmed El-Shamy; Wagdi Elkashef (SpringerOpen, 2019)
Background and aim Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) allows tissue acquisition from solid lesions. The endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) needle was developed to improve diagnostic yield by acquisition of histological core. The impact of the needle type (FNA or FNB) on the diagnostic yield and the technical success needs to be further studied. Therefore, the aim of our study was to compare the diagnostic accuracy and technical success of the 22-G FNA needle with the 20-G procore FNB needle in solid lesions. Patients and methods The study was designed as a pilot study conducted on cases with solid mediastinal, pancreatic, and intra-abdominal lesions, and the patients involved were then randomized for tissue sampling using either the standard 22-G FNA needle or the new 20-G procore FNB needle. Results In this six-month study, 50 patients including 29 male individuals and 21 female individuals, with a mean age of 57.1±12.3 years (range: 15-80 years) were enrolled. No significant difference was detected between FNA 22 G and FNB 20 G as regards the diagnostic accuracy or the technical success rates. However, there was a significant difference in the number of passes needed to reach diagnosis. The success rate of first pass for FNA 22 G and FNB 20 G was 69 and 92.5%, respectively (P=0.014, 95%CI). Conclusion EUS-guided FNA and FNB have comparable diagnostic accuracy for solid lesions. The 20-G FNB needles are easy to handle in anatomically challenging locations and required fewer needle passes to reach diagnosis.